Value of legal education in the process formation of legal culture (Journal of actual problems of jurisprudence, 2018)
In the article the author of a study of legal education and its role in the formation of the legal culture of the Kazakh In the article the author of a study of legal education and its role in the formation of the legal culture of the Kazakh society. Much attention is paid to the essence and nature of legal education, his features. The author highlights issues concerning ways to improve the system of legal education in a holistic pedagogical process, based on the competence approach. In addition, the paper analyzes the main problems of legal education and the ways of their solution, as well as issues of quality of training of graduates of law schools. Scientific work is based on the national and international research, covering the issues of legal education and the ways of its improvement. The author believes that the credibility of the legal system and the level of legal awareness of the population is largely dependent on the degree of qualification of specialists in the field of jurisprudence. The article shows that the level of the legal profession largely depends not only on the efficient functioning of the mechanism of legal regulation, but also the attitude of ordinary citizens to the law and legal phenomena.Key words: legal education, legal culture, legal ideology, culture, democratic state, civil society, state, society, legal consciousness, democratic state and its values.